(untitled) (Global Journal of Human-Social Science, 2013)
This article highlights secularization debate; identifying its major variants; critiquing the idea with particular reference to Peter Berger’s rendition; and presenting his recent position on the debate. The paper then provides a snapshot of development from the Western perspective, examining the relationship between religion and development, showing how it differs from an African perspective. The paper argues that,the Western models of development are not compatible with Africa because they are alien, incompatible with the norms and values of most Africans, and notably, neglect or relegate several important aspects of the people’s culture, including the role of religion in development.Thus, when African leaders embrace and applaud the Western-based idea of secularized development at the expense of the subalterns, who do not feel the impacts of these superficial developments, it becomes a terrific façade. The article concludes by proposing a bottom-up approach to development conception and implementation in non-Western society, notably Africa, asserting that it has to beconsidered as a process compatible with the people’s realities, reflecting their values, including religion and culture generally.